Psychophysiological restorative potential in cancer patients by virtual reality (VR)-based perception of natural environment - Song, Rui; Chen, Qujing; Zhang, Ying; Jia, Qing'an; He, Hongyun; Gao, Tian; Qiu, Ling (Frontiers in Psychology, 2022)
The positive significance of nature to human' self-reported well-being has been widely confirmed, but less attention has been paid to the study of cancer patients, as well as the role of time on the restorative effects. Therefore, using virtual reality (VR) and the inclusion of patients with esophageal and gastrointestinal cancer as participants, this study conducted indoor experiments to explore patients' psychophysiological recovery through the perception of five different environmental types with three to five interventions per week. There were 63 participants selected from the People's Hospital in Shaanxi Province. Depending on their psychophysiological state, they would participate in three to five interventions in a week to compare the number of interventions needed to achieve maximum restoration. The five environmental types utilized varied in land cover, vegetation structure and landscape characteristics, and were identified as blue space (BS), open green space (OGS), semi-open green space (SOS), closed green space (CGS) and grey space (GrS). Before and after viewing landscapes, the changes of psychophysiological indicators were measured to explore the influence of different environmental types on participants. The results showed that the participants preferred and received the highest perceived restorative potentials in BS and lastly, GrS. The green and blue spaces measurably increased positive emotions and perceived restoration while a decreasing negative emotions and the heart rate (HR) compared with the GrS. Participants had the highest level of relaxation while their eyes were closed in the EEG baseline stage. Moreover, participants received the most relaxation when they contacted with nature three times a week, which indicated that excessive natural participation may not be conducive to the sustained development of cancer patients' psychophysiological health. Instead of field appreciation, VR could be utilized to increase the access of cancer patients to nature and then be used as an approach to landscape interaction.